Escherichia coli Nissle 1917 Protects Intestinal Barrier Function by Inhibiting NF-κB-Mediated Activation of the MLCK-P-MLC Signaling Pathway. (3rd July 2019) - Guo, Shihao; Chen, Shanwen; Ma, Ju; Ma, Yongchen; Zhu, Jing; Ma, Yuanyuan; Liu, Yucun; Wang, Pengyuan; Pan, Yisheng
Abstract : Escherichia coli Nissle 1917 (EcN), a kind of probiotic, has been reported to have a protective effect on the intestinal barrier function and can ameliorate certain gastrointestinal disorders. In this study, the potential protective effect of EcN on the intestinal barrier function in a septic mouse model induced by cecal ligation and puncture (CLP) operation was investigated. FITC-Dextran 4, 000 Da (FD-4) flux and the expression levels of tight junction (TJ) proteins were measured to evaluate the protective effect of EcN on the intestinal barrier function. Then, Caco-2 monolayers were utilized to further investigate the protective effect of the EcN supernatant (EcN sup ) on the barrier dysfunction induced by TNF- α and IFN- γ in vitro; the plasma level of both the cytokines increased significantly during sepsis. Transepithelial electrical resistance (TEER) and FD-4 transmembrane flux were measured, and the localization of ZO-1 and Occludin was investigated by immunofluorescence. The expression of MLCK and the phosphorylation of MLC were detected by western blot. The activation of NF- κ B was explored by immunofluorescence, and CHIP assays were performed to investigate the conjunction of NF- κ B with the promoter of MLCK. The results indicated that EcN protected the intestinal barrier function in sepsis by ameliorating the altered expression and localization of TJ proteins and inhibiting the NF- κ B-mediated activation of the MLCK-P-MLC signaling pathway which might be one of the mechanisms underlying the effect of EcN.